Pelestarian Kearifan Lokal Beryajna Melalui Edukasi Budidaya Tanaman Kelapa Upakara Di Desa Bunutin - Sri Yudari, A. A. Kade; Karmini, Ni Wayan; Ngurah, I Gusti Ayu; Sriwinarti, Ni Nyoman (Jurnal Penelitian Agama Hindu, 2023)
The implementation of rituals in Bali is form of local wisdom from generation to generation. The local wisdom of yajna with the support of coconut facilities continues to be socialized, understood and interpreted in the form of knowledge, customary norm, cultural values and community behaviors carrying out various rites in Bunutin Village. This study aims to motivate the community through education on the importance of coconut cultivation and its positive impacts and benefit in religious life. The research design used a qualitative-methods based on the phenomenon of coconut scarcity during observations and interviews.The research is studied with a phenomenological perspective to generate the objective nature of human consciousness based on knowledge, experience in life. The results of the study show that the people in Bunutin Village enthusiastic about appreciating, feeling motivated and raising their awareness, understanding the need for cultivating the upakara coconut plants they seem quite active in seeking sulotions to overcome the scarcity of ritual facilities. The emergence of awareness cannot be separated from the role of motivators in educating the public in order to achieve the goal of preservation through the provision of coconut raw material which is sufficient and balanced with the intensity of the yajna implementation.